PERLINDUNGAN HUKUM TERHADAP HAK TERDAKWA DALAM PROSES PERSIDANGAN PERKARA KEKERASAN DALAM RUMAH TANGGA - Samuel Sandi Giardo Purba; Firdaus '; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Criminal Procedure Law Reform in Indonesia has upheld the protection of human rightsissues. But in practice, this often happens violations committed by the Judge as enforcershukum.hakim in fact often ignore the rights owned by the defendant, particularly related rights legalaid under Article 56 Criminal Procedure Code. As the case law that occurred in the region Siakdistrict court with the case number: 36Pid.B / 2008 / PN.SIAK that the trial the defendant is not legalcounsel.As for the purpose of this thesis, namely; First, to find out why the threatened criminaldefendant 5 years or older who are not able to compulsory legal counsel in the trial process, Second,to determine whether the proceedings may be continued against the defendant that criminalized 5(five) years or more that no legal counsel , Third, To know how the legal consequences if convicteddefendant five (5) years or more is not legal counsel.This type of research can be classified in this type of normative research, ie, with a case studyof the crime of domestic violence that occurred in the region Siak District Court law, and also takingor collecting data with a wide variety of reference contained in the literature through reading books,legislation, the materials of the website on the internet, and other reference sources that has to dowith the material of this thesis.From the research, there are three main things that can be inferred. First, the defendant ispunishable five (5) years or older who are not able to compulsory legal counsel in the proceedingsbecause the right to legal assistance concerns the defendant's rights set out in the Indonesianconstitution, the Second, the trial process can be continued even if the defendant is imposed with 5(five) years or more without legal counsel, because in the laws and regulations do not exist on thearticle which asserted that the trial judge can not proceed if the accused is punishable 5 years ormore is not legal counsel, Third, the legal consequences if the accused is punishable five (5) years orolder who are not legal counsel when the trial court made the process becomes null and void, adviceauthor, First, it helps the government to socialize about the rights of the accused when the court, inorder litigious society and able to fight for their rights recognized law, Second, the judge inconducting the examination in the trial, should truly uphold a sense of justice by applying theprinciples akusator, where the defendant in the court of law is not an object subject sebgai law.Third, Hope to government officials in charge of the manufacture of the Act, so that articleconcerning the rights of legal aid for indigent defendants along with legal sanctions if violated, orderthe defendant's rights are fully protected, in order to attain justice amidst community.